Paulo Freire: Voices and silences1. Issue 13 (13th December 2022) - Torres, Carlos Alberto
Abstract: Freire is one of the most powerful voices challenging the hegemony of bureaucratic and banking educational systems. His voice was particularly influential impacting revolutionary processes and progressive social movements while at the same time learning from their practices. However, some silences in his oeuvres requires further examination. In this article, we focus on the silences of Freire regarding education and its relationship with work and labor, gender issues, and citizenship building.